STRATEGI PENGEMBANGAN KOPERASI UNIT DESA (KUD) MINA TELUK SEMANGKA DI KECAMATAN KOTA AGUNG PUSAT KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Anitha Andarrini T; Dyah Aring Hepiana Lestari; Indah Nurmayasari (Lampung University, 2020)
This research aims to analyze the internal and external environment, formulate development strategies, and determine the priority strategies of KUD Mina Teluk Semangka. This research uses a case study method. Respondents involved 13 people consisting of administrators and members of cooperatives, experts and regulators. Data analysis methods used are qualitative descriptive analysis, SWOT analysis, and QSPM. The results indicated that internally, cooperatives have the main strength on its business units that are complement each other and suitable to the needs of members, while the main weakness is on the absence of processing.to add value of the products Externally, cooperatives face great opportunities on high level of demand on fish and face the main threat on lack of public awareness in working together. The priority strategies that can be used in developing cooperatives are as the following: utilizing and enhancing the ability of members to diversify their products using fishery product processing technology, collaborating with the government and other parties in creating tourism-based business unit, utilizing trained human resources to overcome limitations in keeping up with technological developments, and increasing awareness of the community in cooperation and members in paying mandatory savings.Key words: cooperative, fisheries, SWOT analysis, QSPM